Understanding and teaching the modern Middle East - El Shakry, Omnia S., 1970- (Harvey Goldberg series for understanding and teaching history., 2020)
Understanding and Teaching the Modern Middle East moves away from the Orientalist frameworks that have dominated the West's understanding of the region, offering a range of fresh interpretations and approaches for teachers. The volume brings together experts on the rich intellectual, cultural, social, and political history of the Middle East, providing necessary historical context to familiarize teachers with the latest scholarship.